Reconstructing Dual‐Induced {0 0 1} Facets Bismuth Oxychloride Nanosheets Heterostructures: An Effective Strategy to Promote Photocatalytic Oxygen Evolution. Issue 5 (28th March 2019) - Ning, Shangbo; Shi, Xiaoqi; Zhang, Hongwen; Lin, Huaxiang; Zhang, Zizhong; Long, Jinlin; Li, Yi; Wang, Xuxu
Abstract : Sunlight‐driven photocatalytic water splitting to generate oxygen (O2 ) is a promising approach for utilizing solar energy. Herein, direct Z‐scheme heterostructure photocatalysts composed of ultrathin Bi3 O4 Cl and BiOCl nanosheets are rationally fabricated via alkaline chemical etching and solvent exfoliation for O2 evolution under visible light. With AgNO3 and FeCl3 as the electron scavenger, the optimized ultrathin Bi3 O4 Cl/BiOCl exhibits prominent photocatalytic activity for O2 production under visible‐light illumination and the production rate (Fe 3+ : 58.6 µmol g −1  h −1 ) is much higher than the nanocrystal heterostructure (Fe 3+ : 28.5 µmol g −1  h −1 ). This ultrathin heterostructure system can efficiently transfer the electrons, which leads to a considerable improvement in the photocatalytic performance. Due to the suitable band edge potentials and the intense electronic interaction between two‐dimensional (2D) Bi3 O4 Cl and 2D BiOCl, as confirmed by theoretical computations, photoluminescence, and photoelectricity tests, the ultrathin heterojunction with an internal electric field has a highly remarkable charge transfer. The intimate interface contact and {0 0 1} facets effect promote the high photocatalytic performance of the ultrathin Bi3 O4 Cl/BiOCl heterostructure. Abstract : The ultrathin Bi3O4Cl/BiOCl nanosheets heterostructure system can efficiently transport electrons, which leads to a considerable improvement in the photocatalytic performance. The ultrathin heterojunction with an internal electric field enables remarkable charge transfer and the {0 0 1} facets effect within the intimate interface contact promotes the high photocatalytic oxygen evolution.